2004
DOI: 10.1023/b:bire.0000037753.76657.94
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Antiandrogen Flutamide on the Expression of Protein Kinase C Isoenzymes in LNCaP and PC3 Human Prostate Cancer Cells

Abstract: Flutamide is a nonsteroidal antiandrogen that is frequently used for total androgen blockage in the treatment of advanced prostate cancer. We investigated the effect of this antiandrogen on the expression of protein kinase C (PKC) isoenzymes (a, b1, e, f) that are involved in cell growth, apoptosis and neoplastic transformation. Androgen-dependent (LNCaP) and independent (PC3) human prostate cancer cells were cultured in a medium that contained fetal bovine serum (FBS) or charcoal-stripped serum (CSS) and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Of note, the flutamide-induced KLF9 expression can be efficiently attenuated by DHT, indicating that the activation of KLF9 expression by flutamide was due to its capability in blocking the action of androgen in cells. Interestingly, it has been reported that flutamide can behave as an AR agonist in certain circumstances [3,23]. The bi-directional effects of flutamide on cell survival may be related to the different status of AR in cells, the dose of the drug and the cultured medium used in the experiments [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the flutamide-induced KLF9 expression can be efficiently attenuated by DHT, indicating that the activation of KLF9 expression by flutamide was due to its capability in blocking the action of androgen in cells. Interestingly, it has been reported that flutamide can behave as an AR agonist in certain circumstances [3,23]. The bi-directional effects of flutamide on cell survival may be related to the different status of AR in cells, the dose of the drug and the cultured medium used in the experiments [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The growth of PCa is initially androgen-dependent, and anti-androgens (flutamide, nilutamide, bicalutamide, etc. ), as one type of the androgen deprivation therapy, are capable of inducing apoptosis of tumor cells and thus constitute the basis of endocrine therapy for PCa [2][3][4][5]. However, most PCa cells eventually become androgen-independent, which results in the failure of androgen deprivation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Androgen ablation therapy using luteinizing hormone-releasing hormone agonists (LH-RH) has become a primary treatment for metastatic prostate cancer [22]. LH-RH antagonist Cetrorelix inhibits the growth of PC-3 through downregulation of EGF receptors whereas antiandrogen Flutamide affects the expression of protein kinase C (PKC) which is important for prostate cancer cell growth [23, 24]. Anti-androgens are frequently used in conjunction with androgen ablation therapy as a combined androgen blockade to improve therapeutic outcome [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, if our present data resulted from the agonistic action of FL in PMCs, both T and DHT should be expected to up-regulate circadian Per2 gene oscillations. Recent studies also reported the AR-independent action of FL [40,41]. FL activates the expression of protein kinase C isoenzymes in CSS-LNCaP cells and can elicit responses in prostate cancer cells that do not express AR [40].…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies also reported the AR-independent action of FL [40,41]. FL activates the expression of protein kinase C isoenzymes in CSS-LNCaP cells and can elicit responses in prostate cancer cells that do not express AR [40]. In the rat prostate, apoptosis is suppressed by binding of decoy receptor DcR2 to TNF--related apoptosis-inducing ligand and is induced through the decoy receptor inhibited by FL [41].…”
Section: Discussionmentioning
confidence: 97%